A integração fronteiriça Brasil-Uruguai e o projeto de saneamento urbano integrado Aceguá-Acegua - Tonel, Daniela Schneider (2018)
The focus of the present study is on the construction and implementation process of the Integrated Urban Sanitation Project in Aceguá-Acegua cities (PSUIAA), both located on the border between Brazil and Uruguay. It is particularly important to understand how the process itself took place and whether the sanitation project in question shows the deepening of the regional integration process. It is also interesting to analyze the role of local people in the process. For that effect, official documents as well as others from different sources were used, such as of bibliographical nature, magazines, electronic media archives and legal documents. In addition to these after mentioned sources, semistructured interviews were conducted with local political people. The methodology chosen for the analysis of these data was qualitative documentary analysis and oral history. Hence, the present work is inserted in the debate about regional integration processes, more specifically about the infrastructure of the integration processes as part of a political process.